2015
DOI: 10.1109/jstqe.2015.2420595
|View full text |Cite
|
Sign up to set email alerts
|

1.3-μm InGaAs MQW Metamorphic Laser Diode Fabricated With Lattice Relaxation Control Based on In Situ Curvature Measurement

Abstract: We demonstrate a lattice relaxation control by in situ curvature measurement for a metamorphic buffer. Using this relaxation control, we investigated a thin (240 nm) In 0 .15 Ga 0 .85 As metamorphic buffer for fabricating an unstrained In 0 .10 Ga 0 .90 As quasi-substrate on a GaAs substrate and succeeded in fabricating a 1.3-μm metamorphic InGaAs multiplequantum well laser diode (LD) on the metamorphic buffer. We confirmed that the LD was directly modulated at 25 Gb/s with a high-characteristic temperature (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Over the past several decades significant research effort has been dedicated to the development of III-V semiconductor alloys and quantum-confined heterostructures such as quantum wells [1][2][3][4][5][6] and quantum dots, [7][8][9][10] as platforms for the development of a range of photonic, photovoltaic, and spintronic devices. Despite the widespread of use InP-based quantum well (QW) based devices in optical communications, an important factor limiting overall device performance is the prevalence of temperature-dependent loss mechanisms, including carrier leakage, as well as non-radiative Auger recombination and inter-valence band absorption (IVBA) processes involving transitions between the highest energy valence bands (VBs) and the spin-split-off (SO) band.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several decades significant research effort has been dedicated to the development of III-V semiconductor alloys and quantum-confined heterostructures such as quantum wells [1][2][3][4][5][6] and quantum dots, [7][8][9][10] as platforms for the development of a range of photonic, photovoltaic, and spintronic devices. Despite the widespread of use InP-based quantum well (QW) based devices in optical communications, an important factor limiting overall device performance is the prevalence of temperature-dependent loss mechanisms, including carrier leakage, as well as non-radiative Auger recombination and inter-valence band absorption (IVBA) processes involving transitions between the highest energy valence bands (VBs) and the spin-split-off (SO) band.…”
Section: Introductionmentioning
confidence: 99%
“…Our next challenge to developing MQW LDs emitting at 1.3 μm is growth of a metamorphic InGaAs buffer layer on the GaAs/Ge layers. Since all metamorphic InGaAs LDs were grown on on-axis GaAs (100) substrate [17]- [19], it is necessary to develop techniques that enable us to grow metamorphic InGaAs layers on misoriented substrates or antiphase-domain-free GaAs layers on on-axis Si substrates.…”
Section: Gaas Buffer Layer Growth and Annealingmentioning
confidence: 99%
“…To elongate the emission wavelength of the MQWs to 1.3 μm, the GaAs/Ge/Si structure incorporates an InGaAs metamorphic buffer layer. The details of the metamorphic buffer and performance of the LDs on GaAs substrate are described elsewhere [17]- [19].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, since 1994, when the first metamorphic InGaAs/GaAs telecom laser was reported by Uchida et al, only a few working lasers were reported reaching beyond 1.3 μm telecom wavelength, all fabricated using molecular beam epitaxy (MBE), , while metalorganic vapor-phase epitaxy (MOVPE) surprisingly failed in obtaining meaningful results. However, using MOVPE, Nakao et al recently achieved 1.3 μm operation with native QW photoluminescence at 1.27 μm. It is worth stressing that no explanation nor discussion is present in the literature on the limiting factors associated with the MOVPE growth of such structures nor how to overcome them.…”
Section: Introductionmentioning
confidence: 99%